PARTISIPASI PEMUKA MASYARAKAT DALAM PENGELOLAAN PERPUSTAKAAN DESA - Daeng Ayub; Anindita Yulisman; Muhammad Jais (STKIP Pesisir Selatan, 2022)
This research was conducted with the aim of knowing and describing the participation of community leaders in the management of village libraries in Desa Segati Kecamatan Langgam Kabupaten Pelalawan. The method in this research is descriptive research with a qualitative approach. The object of the research is participation, community leaders, and village libraries and the research subjects are community leaders, totaling 4 (four) people. Participation in ideas and social participation which is given as a closeness of heart is the participation that is most often carried out by community leaders. This is because participation is a very easy, flexible and timeless form of participation. In addition, labor participation, skill participation is participation carried out by community leaders but still has limited time and opportunities due to differences in work and opportunities from each community leader in Desa Segati Kecamatan Langgam Kabupaten Pelalawan. Meanwhile, property participation has been carried out by several community leaders indirectly.